Enhancing hygroscopic stability of agave fructans capsules obtained by electrospraying - Ramos-Hernández, Jorge A. (J Food Sci Technol, 2020)
In this work, different whey protein (WP) ratios (5, 10, 20, 30, 40 and 50% w/w) were added as stabilizers to high degree of polymerization Agave fructans (HDPAF) capsules to decrease the hygroscopicity. Results showed that the WP and HDPAF in 1:520:80 ratio (20/80 w/w) decreased significantly the hygroscopicity of capsules from 12.19 to 8.34%. Additionally, this polymeric mixture was assessed for the encapsulation of sea grape (Coccoloba uvifera L.) leaf extract was achieved by via electrospray, using this biopolymers mixture. Scanning electron microscopy (SEM) images exhibited spherical particles with sizes from 655 to 7250 nm. The thermal stability of encapsulated extract was demonstrated by via thermogravimetric analysis. The in vitro release study in simulated stomach (0–180 min) and intestine conditions (0–300 min) showed the controlled release of the controlled release of the encapsulated extract. The encapsulated extract and its bioavailability in simulating the stomach (0–180 min) and small intestine (0–300 min) Therefore, HDPAF–WP is a viable option as an encapsulating matrix susceptible to be used in the food, pharmaceutical, and cosmetic industries.